Efficacy of catheter ablation of focal sources in persistent atrial fibrillation - Takahashi, Yoshihide; Yamashita, Syu; Suzuki, Masahito; Yabe, Kento; Hirao, Kenzo (Journal of Cardiovascular Electrophysiology, 2018)
Introduction Recent studies suggest that atrial fibrillation (AF) is maintained by electrical activity arising from focal sources. We sought to test whether catheter ablation that targets focal sources can improve on current ablation protocols for persistent AF. Methods and results In patients with persistent AF whose AF did not terminate with pulmonary vein (PV) isolation, the left atrium was mapped with a 20‐pole high‐density mapping catheter using CARTO®3 navigation. If a site demonstrated centrifugal activation over at least three consecutive cycles, it was deemed a focal source and ablated. If AF remained, defragmentation was performed until AF was terminated. Freedom from atrial tachyarrhythmia was compared between the study patients and propensity score matched historical controls who had undergone conventional stepwise ablation. Of the 68 study patients, 2.9 ± 1.9 focal sources were identified in 60 patients. Focal sources displayed transient centrifugal activation patterns for a median of six consecutive cycles. Total radiofrequency duration was shorter in the study group (62 ± 16 minutes vs. 75 ± 24 minutes, P = 0.0003). During a 1‐year follow‐up period, 39 (57%) and 26 (38%) patients were free from atrial tachyarrhythmias in the absence of antiarrhythmic drugs in the study and control groups, respectively (hazard ratio: 1.85, 95% confidence interval: 1.17–2.96, P = 0.009). Improvement of clinical outcome was mainly driven by a decrease in recurrence of atrial tachycardia in the study patients (22% vs. 40%, P = 0.047). Conclusion The results of this study suggest that focal sources are appropriate ablation targets in addition to the PVs in persistent AF.